Pengembangan E-Modul Berbasis Model RME (Realistic Mathematics Education) Menggunakan Rumah Pangeran Duayu untuk Meningkatkan Kemampuan Pemecahan Masalah Pada Materi Keliling dan Luas Bangun Datar Kelas IV SD - Sadela Nurhayani; Agus Susanta; Irwan Koto (UNIB Press, 2024)
This study aims to determine the feasibility of the material, language, design, teacher and student responses, as well as the effectiveness of the product resulting from the development of an RME-based e-module using the